2022
DOI: 10.3390/bs12080265
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Apps for People with Schizophrenia: How Feasible Are m-Health Approaches?

Abstract: Background: The large health disparities among those diagnosed with schizophrenia urgently need to be addressed. These disparities are partially caused by adverse health behaviours such as smoking. Smoking cessation apps vary in efficacy across various populations, and there are concerns regarding the accessibility and usability of apps for people with schizophrenia. Objective: This review identifies and examines the feasibility of using apps for smoking cessation in people with schizophrenia. Methods: A non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Results suggest that mHealth interventions are effective in improving cancer patients’ physical activities and diet. Sawyer et al [ 32 ] research shows that mHealth smoking cessation apps can be feasible and acceptable. Additionally, Mamom and Daovsan [ 33 ] evaluate telenursing for caregivers to prevent and treat pressure injury in bedridden patients during the COVID-19 pandemic in Thailand.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Results suggest that mHealth interventions are effective in improving cancer patients’ physical activities and diet. Sawyer et al [ 32 ] research shows that mHealth smoking cessation apps can be feasible and acceptable. Additionally, Mamom and Daovsan [ 33 ] evaluate telenursing for caregivers to prevent and treat pressure injury in bedridden patients during the COVID-19 pandemic in Thailand.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…By analyzing results among different groups of patients, overall, studies have demonstrated that smoking cessation apps are feasible for use among people diagnosed with mental illness, especially those with a high score on the System Usability Scale [ 37 ]—a reliable tool for measuring the ease of use of a wide variety of products and services, including hardware, software, mobile devices, websites, and applications. However, it appears clearly that apps designed specifically for patients with schizophrenia or other mental illnesses may be more accessible and user-friendly [ 38 ], emphasizing the importance of end user involvement in app development.…”
Section: Evidence Of Mhealth Focused On Smoking Cessationmentioning
confidence: 99%
“…More recently, app-based approaches have also been well received among this population for self-management of lifestyle behaviours (e.g. nutrition habits [14] and smoking [15]), as well as more complex outcomes (e.g. cognition [16 ▪▪ ,17] and social functioning [18]).…”
Section: Introductionmentioning
confidence: 99%